Model Pembobotan Maks-Min Termodifikasi untuk Menyelesaikan Masalah Pemilihan Supplier Multi-Objektif Fuzzy dengan Fungsi Objektif Fuzzy dan Kendala Fuzzy pada Rantai Supply - Grandianus Seda Mada (Fakultas Pertanian, Universitas Timor, 2019)
Supplier selection is one of the most important activities in supply chain network of a company. Supplier selection can be seen as a multi-objective problem because it is a multi-criteria problem that includes qualitative and quantitative factors. In fact, information relating to the objectives and constraints faced in the supplier selection problem are not known with certainty. Fuzzy set theory can be used in the obscurity and inaccuracy of information. So then the problem of supplier selection can be seen as a fuzzy multi-objective linear program. In business activities in general, between one goal with another goal has a different level of importance for decision makers so that the fuzzy decisions used are non-symmetrical fuzzy decisions. Previously there was a model developed to solve a non-symmetrical fuzzy multi-objective supplier selection problem, namely the weighted additive model. In this paper, the weighted max-min method is developed to deal with the deficiencies of the weighted additive model. In determining the objective function weights, the Analytic Hierarchy Process approach is used. This proposed model can help decision makers find out the right order for each supplier, and enable purchasing managers to manage supply chain performance on cost, quality and service. Finally, a numerical example is given to explain the differences of the two models